Remote PC Wake-On Design Manufacture in Mujahidin Mosque at Candi Mendut - Rizki Priya Pratama (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2021)
There are several methods to turn on a PC from other places, one of which is WOL (wake-on lan). This method requires modem configuration to enable WOL and port forwarding features. However, if it is not possible, there is one method offered by the researcher. The method is creating a system that functions to turn on the PC via the MQTT protocol. This system consists of electronic devices and android applications. Both can be connected to the internet network. The function of this device is to connect the PWRBTN and GND pins for 0.3 seconds. While the android application "Remote wake-on PC Masjid Mujahidin" is a user interface to receive and send data to the device. From the experiment, it was found that this device was controlled from the internet with an android application successfully. In addition, there is information about the status of the PC, the system voltage on the device, and the temperature and voltage of the PC room on the android application. All this information is successfully transmitted from the PC-enabled device to the android application. Terdapat beberapa metode untuk menghidupkan PC dari keadaan mati/off, salah satunya adalah WOL (wake-on lan). Metode ini membutuhkan konfigurasi modem untuk mengaktifkan fitur WOL dan port forwarding. Namun, apabila tidak bisa, terdapat satu metode yang ditawarkan oleh peneliti. Metode tersebut adalah sebuah sistem yang berfungsi untuk menghidupkan PC melalui protokol MQTT. Sistem ini terdiri dari sebuah perangkat elektronik dan aplikasi android yang dapat terhubung pada jaringan internet. Perangkat ini bertugas untuk meng-on-kan PC dengan cara menghubungkan pin PWRBTN dan GND selama 0,3 detik. Sedangkan aplikasi android “Remote wake-on PC Masjid Mujahidin” sebagai user interface untuk menerima dan mengirimkan data ke perangkat. Dari pengujian, didapatkan bahwa perangkat ini berhasil dikendalikan dari internet dengan aplikasi android. Selain itu juga, terdapat informasi mengenai status PC, tegangan sistem pada alat serta suhu dan tegangan ruang PC pada aplikasi android. Semua informasi ini berhasil dikirimkan dari peralatan wake-on PC ke aplikasi android.